Addressing the Links among Agriculture, Malaria, and Development in Africa - Asenso-Okyere, Kwadwo; Asante, Felix Ankomah; Tarekegn, Jifar; Andam, Kwaw S. (International Food Policy Research Institute, 2012)
The global impact of malaria on human health, productivity, and general well-being is profound, and Africa has been particularly hard hit. In 2006, more than 90 percent of deaths from malaria occurred in Africa, where 45 of the 53 countries are endemic for the disease (WHO 2008). Malaria costs Africa more than US$12 billion annually, and it slows economic growth in African countries by as much as 1.3 percent per year (WHO 2010).